Marhata Sinamot at Toba Ethnic Wedding Ceremony: Antropolinguistics Study - Ma Samuel Rt Simanjuntak; Flansius Tampubolon; Jamorlan Siahaan (Budapest International Research and Critics University, 2021)
The scientific title is